Locus Coeruleus tracking of prediction errors optimises cognitive flexibility: An Active Inference model - Sales, Anna C.; Friston, Karl J.; Jones, Matthew W.; Pickering, Anthony E.; Moran, Rosalyn J. (PLOS Computational Biology, 2019)
Author summary The brain uses sensory information to build internal models and make predictions about the world. When errors of prediction occur, models must be updated to ensure desired outcomes are still achieved. Neuromodulator chemicals provide a possible pathway for triggering such changes in brain state. One such neuromodulator, noradrenaline, originates predominantly from a cluster of neurons in the brainstem—the locus coeruleus (LC)—and plays a key role in behaviour, for instance, in determining the balance between exploiting or exploring the environment. Here we use Active Inference (AI), a mathematical model of perception and action, to formally describe LC function. We propose that LC activity is triggered by errors in prediction and that the subsequent release of noradrenaline alters the rate of learning about the environment. Biologically, this describes an LC-cortex feedback loop promoting behavioural flexibility in times of uncertainty. We model LC output as a simulated animal performs two tasks known to elicit archetypal responses. We find that experimentally observed ‘phasic’ and ‘tonic’ patterns of LC activity emerge naturally, and that modulation of learning rates improves task performance. This provides a simple, unified computational account of noradrenergic computational function within a general model of behaviour.